Data integration in the life sciences : 11th International Conference, DILS 2015, Los Angeles, CA, USA, July 9-10, 2015, Proceedings /: 11th International Conference, DILS 2015, Los Angeles, CA, USA, July 9-10, 2015, Proceedings. (2015) - Unknown
No abstract available